Crystallisation in polymer nanocomposites - Jog, Jyoti Prakash (Materials Science and Technology, 2006)
Polymer nanocomposites are of interest as they exhibit extraordinary properties compared with the base polymer. The second phase dispersed in the polymer matrix can be carbon nanotubes, semi-conducting inorganic nanoparticles or layer silicates such as clay. Crystallisation in these materials is also of great interest. Polymers exhibit structures at various scales (e.g. lamella, unit cell and spherulites) and the presence of a second phase has a profound effect on crystallisation. General trends observed include acceleration/retardation of crystallisation, changes in spherulite morphology and, in a few cases, changes in the crystal structure. All these observations relate to the presence of a micrometre scale second phase. However, when the dimensions of the second phase are close to the chain dimensions, the effects on crystallisation become particularly interesting. An attempt is made in the present review to address the effect of a nanoscale second phase on aspects such as isothermal and non-isothermal crystallisation, spherulite growth, phase transformation and polymorphism.
Keywords: clay; crystallisation; Nanocomposites; polymer matrix composites

Crystallization and phase transformation kinetics of poly(1-butene)/MWCNT nanocomposites - Wanjale, Santosh D.; Jog, Jyoti Prakash (Polymer, 2006)
Poly(1-butene)/MWCNT nanocomposites were prepared by simple melt processing technique. Crystallization, crystal-to-crystal phase transformation and spherulitic morphology were studied using differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and optical microscopy (OM). The non-isothermal crystallization exhibited higher values of Z, derived from Avrami theory and lower values of F(T) obtained from Avrami-Ozawa analysis, while the isothermal crystallization revealed a significant increase in crystallization temperatures and lower crystallization half times compared to pristine PB. The observed changes in the crystallization kinetics were ascribed to the enhanced nucleation of PB in the presence of MWCNT. The nucleating activity calculated from the non-isothermal crystallization data revealed that the MWCNTs provide an active surface for the nucleation of PB. The optical micrographs exhibited significantly smaller crystallites with disordered morphology for the nanocomposites compared to the well defined spherulitic morphology for pristine PB. The rate of phase transformation from kinetically favored tetragonal to thermodynamically stable hexagonal form was noticeably enhanced as evidenced by the reduction in the half time for phase transformation from 58 h to 25 h for PB reinforced with 7% MWCNT. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: MWCNT; Phase transformation; poly(1-butene)

Viscoelastic and dielectric behavior of poly(1-butene)/multiwalled carbon nanotube nanocomposites - Wanjale, Santosh D.; Jog, Jyoti Prakash (Journal of Macromolecular Science Part B-Physics, 2006)
Linear viscoelastic properties and dielectric behavior of poly(1-butene)/multiwalled carbon nanotube (MWCNT) nanocomposites were investigated. Dynamic mechanical analysis showed significant increase in storage modulus in the rubbery regime. The tan delta peak temperature remained constant; however, the peak intensity was lowered for the nanocomposites. In melt rheological studies the nanocomposites showed a shift in crossover frequency to the lower side, suggesting delayed relaxation of the molecular chains in the presence of MWCNT and this shift was found to depend on the content of MWCNT. The dielectric constant increased from 2.2 to 70 for the nanocomposite with 7 wt. % MWCNT. The electrical conductivity increased significantly, from 10(-15) to 10(-3) S/cm. The results of rheology and dielectric studies indicate that a percolation network is formed that is responsible for the observed changes.
Keywords: Dielectric; MWCNT; poly(1-butene); viscoelastic

Assessing feasibility of polyarylate-clay nanocomposites towards improvement of gas selectivity - Bhole, Yogesh S.; Wanjale, Santosh D.; Kharul, Ulhas K.; Jog, Jyoti Prakash (Journal of Membrane Science, 2007)
Polymer-clay nanocomposites are well known to reduce the penetrant permeability by following tortuous path. Effects of such reduction in gas permeability on variation in selectivity of nanocomposites prepared using a high permeability polymer were examined. The polyarylate: poly (tetramethyl bisphenolA-iso/terephthalate) that exhibits high permeability and moderate selectivity was chosen for making nanocomposites with two organically modified clays (Cloisite 6A and 10A) by solution intercalation method. The nanocomposite formation for various clay loadings (3, 5 and 7% w/w) in polyarylate was ascertained by change in physical properties (X-ray diffraction, DMA, TEM). Behavior of solution viscosity and nanocomposite density indicated existence of polymer-clay layer interactions. As anticipated, though the gas permeability of pure gases, viz., He, N-2, CH4 and CO2 exhibited decrease, it was not monotonous. This decrease was more for larger gases (N-2, CH4 and CO2) in comparison to the decrease for smaller gas (He) permeability. This led to a decrease in CO2/N-2 and CO2/CH4 selectivities and increase in He/CO2 selectivity; while He/CH4 selectivity was increased substantially at 7% clay loading. This variation indicated feasibility of nanocomposites formation as a tool for improving selectivity of certain gas pairs. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Gas permeation; Nanocomposites; polyarylates; selectivity; solution intercalation

Swelling and mechanical behavior of modified poly(vinyl alcohol)/laponite nanocomposite membranes - Nair, Shubhangi H.; Pawar, Kiran C.; Jog, Jyoti Prakash; Badiger, Manohar V. (Journal of Applied Polymer Science, 2007)
Nanocomposite (NC) membranes based on hydrophobically modified PVA and laponite were synthesized with varying laponite content in the feed. The incorporation of laponite in NC membranes was investigated by FTIR spectroscopy and thermogravimetric analysis. The swelling ratio of membranes was determined as a function of temperature and laponite content. Swelling studies of NC membranes exhibited the decrease in swelling with an increase in laponite content in the NC membranes. The swelling ratio of NC membrane with 20% laponite slightly increased with an increase in temperature. Dynamic mechanical analysis showed the systematic increase in storage modulus with laponite content, which indicates the enhancement of mechanical property upon laponite addition. There was also a decrease in the tan 6 peak values of NC membranes with an increase in laponite content in NCs. The permeabilities through NC membranes as a function of solute size and laponite content were studied and the results showed molecular screening based on size. The permeability of solute reduced due to the presence of well-dispersed laponite in the NC. (c) 2006 Wiley Periodicals, Inc.
Keywords: Dynamic mechanical analysis; laponite; membranes; nanocomposite hydrogel; poly(vinyl alcohol)

Copolyester nanocomposites based on carbon nanotubes: reinforcement effect of carbon nanotubes on viscoelastic and dielectric properties of nanocomposites - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Polymer International, 2008)
Nanocomposites based on an amorphous copolyester, poly(ethylene glycol-co-cyclohexane-1,4-dimethanol terephthalate) and carbon nanotubes were fabricated using a simple melt processing technique. The reinforcement effect of carbon nanotubes in the copolyester was investigated experimentally using different approaches based on dynamic mechanical analysis, theology and dielectric analysis. The nanocomposites show a mechanical reinforcement effect with significant increase in the stiffness especially in the rubbery regime with increasing nanotube content. An increase in T-g and a decrease in damping are seen, which are derived from the presence of a percolating superstructure of the filler. Rheological experiments show an increase in storage modulus up to four orders of magnitude. Viscolelastic characterization shows that the percolation threshold is at 3 wt% of nanotubes. Dielectric relaxation spectroscopy confirms the presence of this percolating structure. We conclude that the responses of both rheological and electrical properties are different, although both are related to the formation of a percolating network superstructure of the filler. (c) 2007 Society of Chemical Industry.
Keywords: Carbon nanotubes; dielectric analysis; nanocomposites.; reinforcement; viscoelastic properties

Dielectric relaxations in PVDF/BaTiO3 nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
The present work aims at the study of molecular relaxations in PVDF/BaTiO3 nanocomposites using broadband dielectric spectroscopy. The nanocomposites of PVDF with BaTiO3 ( 10-30% by wt%) are prepared using simple melt mixing method. In dielectric permittivity study, two relaxation processes are identified corresponding to the crystalline, glass transition in the PVDF/BaTiO3 nanocomposites. The peaks shift to higher frequencies as the temperature is increased. Electric modulus formalism is used to analyze the dielectric relaxations to overcome the conductivity effects at low frequencies. In M `' spectra two peaks are observed only at high temperature and low frequency whereas a single relaxation peak appears at low temperatures. The single relaxation peak appearing at low temperatures is the alpha(c) relaxation attributed to crystalline chain relaxation in PVDF and the second relaxation peak which appears only at high temperatures and at a frequency lower than alpha(c) relaxation is identified as MWS relaxation. The temperature dependence of alpha(c) relaxation and MWS relaxation follows Arrhenius type behavior.
Keywords: dielectric spectroscopy; Interfacial polarization; MWS relaxation; Nanocomposites

Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters

Poly(4-methyl-1-pentene)/MWNT nanocomposites - Patil, Prashant A.; Wanjale, Santosh D.; Jog, Jyoti Prakash (E-Polymers, 2008)
Nanocomposites of poly(4-methyl-1-pentene) (PMP) with various weight fractions of multiwall carbon nanotubes (MWNT's) were prepared by melt compounding. The nanocomposites are characterized for structure using scanning electron microscopy. The viscoelastic behavior of the nanocomposites is investigated in solid as well as melt state. The study reveals a significant increase in storage modulus especially in the rubbery regime of the polymer matrix and reduced tan delta. Rheological properties in melt show that the complex viscosity and shear storage modulus are increased as a result of incorporation of MWNT. A systematic decrease in the cross over frequency is noted which is attributed to the increased relaxation time. In dielectric analysis, composition dependent enhanced permittivity and conductivity are observed. The thermal stability of the polymer is found to be significantly improved in presence of MWNT's.

Preparation and characterization of electrospun fibers of nylon 11 - Dhanalakshmi, M.; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
Nylon 11 nanofibers mats were successfully prepared by electrospinning process from formic acid solution. The scanning electron microscopy (SEM) images showed that nanofibers with uniform diameter were produced when the polymer concentration was 10% w/v, whereas ribbons were formed at a higher concentration. The crystalline structure of the nanofibers mats was investigated using X-ray diffraction (XRD) and it was found that the nanofibers mats crystallized in gamma form. The melt crystallized as well as solution casted films however exhibited a form. The thermal properties of these samples were studied using differential scanning calorimetry (DSC) and it was observed that electrospun fibers showed higher crystallinity than the melt-crystallized samples. However, the crystallinity of electrospun fibers was lower than the solution-crystallized sample.
Keywords: biocompatible polymers; electrospinning; Nanomaterials; Nylon 11

Study of dielectric behavior in PVDF/clay nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (E-Polymers, 2009)
A high dielectric permittivity nanocomposite based on poly( vinylidene fluoride) (PVDF) and organically modified clay is reported. The present work aims to study the effect of clay on dielectric behavior of PVDF. The dielectric permittivity study shows a remarkable enhancement in the permittivity of nanocomposites in the low frequency region. The obtained permittivity values fits quite well to the prediction of dielectric permittivity from Vo-Shi model, which takes contribution of interface to permittivity into account. This enhanced permittivity in nanocomposites is attributed to the presence of interfacial polarization. The interface effect is further studied with cole-cole plot analysis. The dielectric loss study of pristine PVDF shows two relaxations associated with segmental (glass transition relaxation) and crystalline chain relaxation. However in the PVDF/Clay nanocomposites crystalline relaxation peak disappears which is attributed to the formation of the beta phase in PVDF/clay nanocomposites.

Influence of filler size and morphology in controlling the thermal emissivity of aluminium/polymer composites for space applications - Babrekar, Harshada A.; Kulkarni, Naveen V.; Jog, Jyoti Prakash; Mathe, Vikas L.; Bhoraskar, S. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The paper has addressed the problem of controlling the thermal emissivities from metal/polymer composites prepared by solution method. Aluminium is used as a filler and polystyrene as a polymer-matrix. Aluminium particles, with micrometer and nanometer dimensions having different morphologies, were employed. The values of emissivities were reduced when the coarse grains and flakes of aluminium were used as fillers, whereas, no significant change was observed when nano-aluminium was used in the composite. Dielectric dispersion for the composites was measured and the results are analysed in view of Fresnel relation. The differences in the values of dielectric constants, between the experimentally measured and those which can be predicted theoretically, are thought to arise from the interfacial polarization. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Camouflaging; Composite; dielectric constant; Infra-red; Thermal emissivity

Production and characterization of a biodegradable poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) copolymer by moderately haloalkalitolerant Halomonas campisalis MCM B-1027 isolated from Lonar Lake, India - Kulkarni, S. O.; Kanekar, Pradnya P.; Nilegaonkar, S. S.; Sarnaik, S. S.; Jog, Jyoti Prakash (Bioresource Technology, 2010)
Several microorganisms produce polyhydroxyalkanoates (PHA). They are accumulated intracellularly as energy storage compounds. The PHAs are of interest because of their potential in biomedical applications. Halophilic bacteria and archaea are known to produce polyhydroxybutyrate (PHB). This paper describes production of a biodegradable copolymer, PHB-co-PHV by a moderately haloalkalitolerant Halomonas campisalis, isolated from Lonar Lake, India. The production of PHA was in the range of 45-81% on dry cell weight basis when the organism was grown in a production medium containing 1% (w/v) maltose and 0.1% (w/v) yeast extract, at pH ranging from 6 to 9 with an inoculum density of 10(5)-10(7) cells/ml of medium, for incubation period of 15-30 h and at 37 degrees C. The polymer produced by the organism is a hydroxyester with molecular weight of 1.3014 x 10(6). Its melting temperature was 171 degrees C. The (1)H NMR analysis revealed that the polymer was a copolymer of PHB-co-PHV. This could be achieved by providing simple carbon source viz. maltose. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable plastics; Halomonas campisalis; Polyhydroxyalkanoates

Characterisation of copolymer, poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) produced by halomonas campisalis (MCM B-1027), its biodegradability and potential application - Kulkarni, Snehal O.; Kanekar, Pradnya P.; Jog, Jyoti Prakash; Patil, Prashant A.; Nilegaonkar, Smita S.; Sarnaik, Seema S.; Kshirsagar, Pranav R. (Bioresource Technology, 2011)
Characterisation of polyhydroxyalkanoate (PHA) film produced by haloalkalitolerant Halomonas campisalis (MCM B-1027) in 14 L SS fermenter revealed it to have composition of monomer units, HB:HV as 96:4 as analysed by (1)H NMR indicating the PHA as a co-polymer of PHB-co-PHV, molecular weight by gel permeation chromatography as 2.08 x 10(6), melting temperature 166.51 degrees C, tensile strength 18.8 MPa; two relaxations namely beta transition corresponding to the glass rubber transition and alpha transition corresponding to crystalline relaxation by Dynamic Mechanical Thermal analysis and only one relaxation corresponding to MWS interfacial polarisation with activation energy of 129 kJ/mol by broadband dielectric spectroscopy. Optical microscopic studies showed typical Maltese-cross pattern of spherulites. The PHA film was found to be biodegradable by standard ASTM method as well as by soil burial method. The leak proof polymer bags prepared from the film could be used as a packaging material. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymer; Copolymer PHB-co-PHV; Dielectric relaxation spectroscopy; Dynamic mechanical analysis; Halomonas

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal

Development of non-woven nanofibers of egg albumen-poly (vinyl alcohol) blends: influence of solution properties on morphology of nanofibers - Rathna, Gundloori Venkata Naga; Jog, Jyoti Prakash; Gaikwad, A. B. (Polymer Journal, 2011)
Egg albumen (EA), a highly functional globular protein with desirable properties, is the least-explored material for biomaterial applications, although it is available in abundance. In our studies, we explored the viability of EA and various blends with biocompatible and non-toxic poly (vinyl alcohol) (PVA) to produce nanofibers for biomedical applications. EA and PVA blends were prepared in various compositions. Electrospinning was used to fabricate non-woven nanofibers. Solution properties, such as viscosity and electrical conductivity, were evaluated for various prepared solutions. Solution viscosity increased with increasing polymer concentration. Solutions with higher contents of EA recorded increased conductivity, which decreased with increasing PVA content. The influence of solution properties on the morphological appearance of as-spun products was studied using scanning electron microscopy. Instead of nanofibers, nanoparticles and microparticles of EA were produced at even higher contents. In contrast, a gradual increase in the addition of PVA content to 8% EA solution resulted in the transformation of particles from large agglomerates to very fine fibers (approximate to 100nm in diameter) because of the influence of polymer content, viscosity and conductivity. The polymer-polymer interactions in the prepared materials have been validated by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and gel electrophoresis. Polymer Journal (2011) 43, 654-661; doi:10.1038/pj.2011.34; published online 18 May 2011
Keywords: Biocompatibility; biodegradable; blends; nanotechnology; Proteins

Enhanced dielectric permittivity in poly (vinylidene) fluoride/multiwalled carbon nanotubes nanocomposite thin films fabricated by pulsed laser deposition - Chanmal, Chetan; Deo, Meenal S.; Jog, Jyoti Prakash (Applied Surface Science, 2011)
The fabrication of high quality thin films of poly (vinylidene fluoride) embedded with multiwalled carbon nanotubes using pulsed laser deposition technique is reported. The prepared films were characterized for structural, morphology and dielectric properties. The morphology analysis revealed uniform dispersion of multiwalled carbon nanotubes throughout the polymer matrix. X-ray diffraction results suggested that the poly (vinylidene fluoride) film is in amorphous phase while addition of multiwalled carbon nanotubes showed presence of crystalline peaks in the nanocomposites films. It was interesting to note that the nanocomposite films exhibits significant enhancement of the ferroelectric beta-phase as evidenced by the X-ray diffraction and Fourier transform infrared spectroscopy results. The dielectric analysis shows a remarkable enhancement in the dielectric permittivity of nanocomposites with lower loss and conductivity level. The results can be attributed to the formation of minicapacitor network and relatively higher percolation threshold in the nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric permittivity; Ferroelectric polymer; Percolation threshold; pulsed laser deposition; Thin films

Low thermal emissive surface properties of ZnO/polyimide composites prepared by pulsed laser deposition - Babrekar, Harshada A.; Jejurikar, S. M.; Jog, Jyoti Prakash; Adhi, K. P.; Bhoraskar, S. V. (Applied Surface Science, 2011)
We report the low thermal-emissive surface properties of composites of ZnO-polyimide. The composites were synthesized by depositing ZnO on polyimide surface by pulsed laser deposition technique. ZnO target was ablated at different incident energy densities and the substrate (polyimide) was held at elevated temperature. This facilitated the c-axis oriented growth of ZnO, which was inferred from the X-ray diffraction analysis. The composites consisted of multilayers having different electrical resistivities. The values of which are also estimated from Hagen-Rubens relation. The reduced infrared emissivities of the composite films, as compared to polyimide, were correlated to the increased carrier concentration and reduced surface resistivity estimated from the Hall measurements. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: pulsed laser deposition; Thermal emissivity; Thin films; Zinc oxide

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.

3D Hexaporous carbon assembled from single-layer graphene as high performance supercapacitor - Yadav, Prasad; Banerjee, Abhik; Unni, Sreekuttan; Jog, Jyoti Prakash; Kurungot, Sreekumar; Ogale, Satishchandra (Chemsuschem, 2012)
Keywords: Electrochemistry; Energy storage; graphene; porous materials; Supercapacitors

Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor

Electrospinning of PHBV/ZnO membranes: structure and properties - Naphade, Rounak; Jog, Jyoti Prakash (Fibers and Polymers, 2012)
Polyhydroxy butyrate-co-valerate (PHBV) - Zinc oxide (ZnO) nano composite fibers were prepared using electrospinning. The structural and optical properties were studied using Fourier transform infrared spectroscopy (FT-ER), X-ray diffraction (XRD) and photoluminescence study (PL). The morphology observed with scanning electron microscope (SEM) revealed no significant changes in the nano composite fibers as compared to bare polymer. The low concentration of ZnO nanoparticles resulted in an increase in overall crystallinity of the polymer matrix which was confirmed from FT-IR and XRD results. The photoluminescence (PL) study indicated the quenching of visible emission in the composite fibers. The ratio of UV to visible emission (I-uv/I-vis) intensity was found to be 12.8 times enhanced in the composite fibers compared to bare ZnO nanoparticles. The nanofibrous mats are self supported and hence offer potential applications in optoelectronic devices and the biomedical imaging.
Keywords: Biomarkers; Biopolymers; electrospinning; ZnO nanoparticles

Enhanced piezoresponse of electrospun PVDF mats with a touch of nickel chloride hexahydrate salt - Dhakras, Dipti; Borkar, Vivek; Ogale, Satishchandra; Jog, Jyoti Prakash (Nanoscale, 2012)
PVDF nanofibers are prepared using electrospinning. The effect of addition of a hydrated salt, nickel chloride hexahydrate (NiCl2 center dot 6H(2)O), on the phase formation is examined. Addition of the hydrated salt (NC) is found to enhance the polar beta phase by about 30%. The peak to peak piezo-voltage generated for PVDF NC is almost 0.762 V, a factor of 3 higher than that for PVDF. The fiber mats exhibit a significantly enhanced dynamic strain sensor response. The voltage generated per unit micro-strain developed during the free vibration test for PVDF was 0.119 mV whereas it was 0.548 mV for PVDF NC, exhibiting a non-linearly enhanced performance vis a vis the increase in the beta phase component.

From small aromatic molecules to functional nanostructured carbon by pulsed laser-induced photochemical stitching - Gokhale, R. R.; Thakare, V. P.; Warule, S.; Lefez, Benoit; Hannoyer, Beatrice; Jog, Jyoti Prakash; Ogale, S. B. (AIP Advances, 2012)
A novel route employing UV laser pulses (KrF Excimer, 248 nm) to cleave small aromatic molecules and stitch the generated free radicals into functional nanostructured forms of carbon is introduced. The process differs distinctly from any strategies wherein the aromatic rings are broken in the primary process. It is demonstrated that this pulsed laser-induced photochemical stitching (PLPS) process when applied to routine laboratory solvents (or toxic chemical wastes when discarded) Chlorobenzene and o-Dichlorobenzene yields Carbon Nanospheres (CNSs) comprising of graphene-like sheets assembled in onion-like configurations. This room temperature process implemented under normal laboratory conditions is versatile and clearly applicable to the whole family of haloaromatic compounds without and with additions of precursors or other nanomaterials. We further bring out its applicability for synthesis of metal-oxide based carbon nanocomposites. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4721268]

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).

Swift heavy ion induced formation of Al/polymer composite layer for low thermal emissivity in the IR range - Babrekar, Harshada A.; Jog, Jyoti Prakash; Mathe, Vikas L.; Avasthi, D. K.; Ojha, S.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2012)
Composites of polymers with aluminium were formed by swift high energy ions of 150 MeV, which are used as low thermal emissivity materials for infrared wavelengths between 8-14 mu m. Emissivity and dielectric constants were studied for these structures. A semi-empirical model has been established to obtain the relation between emissivity and dielectric constant. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: composites; dielectric constant; Swift heavy ion; Thermal emissivity

Synergistic mechanical response of Nylon 6/Trogamid (R) T blends - Ridhore, Amol; Jog, Jyoti Prakash (Journal of Applied Polymer Science, 2013)
Blends of semicrystalline Nylon 6 with a varying ratios of amorphous Nylon are studied for their morphological, thermal, dielectric, and mechanical behavior. Thermal analysis indicated a compositional dependant decrease in the melting and crystallization temperatures of Nylon 6. The blends exhibited a single compositional dependant glass transition temperature in dynamic mechanical thermal analysis and dielectrical relaxation spectroscopy over entire mixing ratio indicating miscibility between the blend components. The values of flexural modulus and tensile modulus of the blends are found to increase without significant loss in the impact properties. The water absorption of the blends is also lower than the values calculated by rule of mixtures. The observed synergistic behavior of the mechanical properties of the blends is indicative of presence of strong interactions in the blends components. (c) 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013
Keywords: blends; dielectric properties; mechanical properties; polyamides; Thermal properties

Surface tailored PS/TiO2 composite nanofiber membrane for copper removal from water - Wanjale, Santosh; Birajdar, Mallinath S.; Jog, Jyoti Prakash; Neppalli, Ramesh; Causin, Valerio; Karger-Kocsis, Jozsef; Lee, Jonghwi; Panzade, Prasad (Journal of Colloid and Interface Science, 2016)
Polystyrene (PS)/TiO2 composite nanofiber membranes have been fabricated by electrospinning process for Cu2+ ions removal from water. The surface properties of the polystyrene nanofibers were modulated by introducing TiO2 nanoparticles. The contact angle of the PS nanofiber membrane was found to be decreased with increasing concentration of TiO2, depicted enhanced hydrophilicity. These membranes were highly effective in adsorbing Cu2+ ions from water. The adsorption capacity of these membranes was found to be 522 mg/g, which is significantly higher than the results reported by other researchers. This was attributed to enhanced hydrophilicity of the PS/TiO2 composite nanofiber membranes and effective adsorption property of TiO2 nanoparticles. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: electrospinning; Metal ion adsorption; Nanofiber; TiO2; Water treatment/purification